(untitled) (Sains Humanika, 2019)
This study aims to research on the effectiveness of M-learning for a lifelong learning learner which is based on the Heutagogy Approach vide the usage of academic writing’s course. Survey has been administrated to 80 students from the executive programme at the Faculty of Education, Universiti Kebangsaan Malaysia in which they have taken academic writing as the compulsory subject of the abovesaid programme. Quantitative data were analysed using descriptive analysis and inference in order to determine the effectiveness of M-learning via heutagogy approach. Result shows that M-learning will increase the heutagogy approach’s element particularly the sharing and connectivity elements. These two elements display highest mean as compared to the other elements. Apart from that, correlation result confirms that heutagogy approach and the students’ response towards technology havepositive relationships which are interconnected between each other. This research will give an implication to the other researcher about heutagogy approachwhich has yet to be fully discovered. Besides that, this research will be beneficial to the public due to the fact that, nowadays, lifelong learning may no longer be conducted via face to face approach, but it can be applied anywhere and anytime via online. On top of that, this research indicates that technology and approach should move along, hand in hand, in building a continuous education in Malaysia. Keywords: heutagogy approach, m-learning; lifelong learning; academic writing